2008
DOI: 10.1111/j.1749-0774.2008.00047.x
|View full text |Cite
|
Sign up to set email alerts
|

Alteration and preservation of cellular characteristics in long-term culture of tetraploid H-1 (ES) cells

Abstract: To examine the alteration in cellular characteristics of polyploid ES cells during long-term culturing, tetraploid H-1 (ES) cells were continuously cultured for 180 days. Cellular DNA content of the tetraploid cells decreased and reached a plateau of 3.3 C, where C represents the complement of haploid chromosomes. The chromosome number also decreased, indicating that the DNA loss was induced by chromosome loss. Cell volume was maintained, suggesting that the DNA loss did not involve cytoplasmic loss. The cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…On the contrary, 4H1 cells lost DNA in long-term culturing (Fujikawa-Yamamoto et al, 2008) and octaploid 8H1 cells transformed to hexaploid teratocarcinoma (FujikawaYamamoto et al, 2009). It has been reported that mouse ES cell/fibroblast hybrid cells with a near-tetraploid karyotype yielded diploid/tetraploid chimeras via injection into C57BL mouse blastocysts, suggesting that the DNA of tetraploid hybrid cells was stable following chimera formation (Kruglova et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the contrary, 4H1 cells lost DNA in long-term culturing (Fujikawa-Yamamoto et al, 2008) and octaploid 8H1 cells transformed to hexaploid teratocarcinoma (FujikawaYamamoto et al, 2009). It has been reported that mouse ES cell/fibroblast hybrid cells with a near-tetraploid karyotype yielded diploid/tetraploid chimeras via injection into C57BL mouse blastocysts, suggesting that the DNA of tetraploid hybrid cells was stable following chimera formation (Kruglova et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…4H1 cells lost DNA content gradually in long-term culturing (Fujikawa-Yamamoto et al, 2008) or abruptly in DME medium . 8H1 cells showed DNA decay where the octaploid cells changed to hexaploid teratocarcinoma in mouse abdomens 2 months after intraperitoneal injection (Fujikawa-Yamamoto et al, 2009).…”
mentioning
confidence: 99%
“…4H1 cells lost DNA content gradually in long-term culturing [14] or abruptly in DME medium [15]. 8H1 cells also showed DNA decay where the octaploid cells changed to hexaploid teratocarcinoma [3].…”
Section: Introductionmentioning
confidence: 95%
“…4H1 cells lost DNA gradually in about 180 days [13]. 8H1 cells also showed DNA decay where the octaploid cells changed to hexaploid teratocarcinoma [3].…”
Section: Introductionmentioning
confidence: 96%